Groundwater Flow in Crystalline Carbonates (Jeseniky Mts., Chech Rep.): Using Stream Thermometry and Groundwater Balance for Catchment Delineation - Jan Kukačka; Viola Altová; Jiří Bruthans; Ondřej Zeman (Acta Carsologica, 2008)
Strips of metamorphosed carbonate rocks in a contact-karst area in the Jeseniky Mts, CzechRepublic, act as aquifers, draining broad areas of crystalline rocks, mostly phyllites. Significant groundwater resources that are partly used as a water supply are in carbonate rocks. Detailed temperature and conductivity measurements coupled withdischarge measurements along all streams in the area demonstrate a relatively quick method to locate virtually all important groundwater outflows from carbonates. Discharge measurements of streams crossing carbonate strips enabled us to locate and quantify the capacity of ponors and losing parts of streams in various water stages. Thanks to a detailed knowledge of losing and gaining parts of streams, we were able to select appropriate profiles to separate catchments withdiffering hydrologic balances (balanced, gaining, losing). Flow directions in carbonates and recharge and discharge areas were delineated by comparing the specific discharges of individual catchments. Resulting flow directions agree withtracer tests in the area. Our outlined approachcan be used in many other areas to locate hidden inflows into streams and to estimate flow between individual small catchments, and it may partly compensate for tracer tests as it allows flow directions to be estimated from hydrological balance and rock geometry.